Managing Marketing Assets for Sustained Returns - American Productivity & Quality Center; American Productivity & Quality Center (APQC American Productivity & Quality Center, 2003)
Based on a consortium benchmarking study organized by APQC and ARF, this report follows APQC's and ARF's 2001 Best-practice Report "Maximizing Marketing Return on Investment". The focus of this new report is broader in nature to examine how leading organizations manage brand and customer assets by using processes for a sustained return on their marketing investments. Key findings focus on: understanding marketing assets by identifying and valuing assets and defining stewardship over assets; leveraging assets by using marketing ROI metrics to develop and adjust a marketing budget aligned with the brand/asset value and leverage potential; and creating synergy for marketing assets by tracking asset performance and evaluating where interactions among marketing programs may lead to shortfalls or unexpected successes. This Best-practice Report takes a different approach from traditional benchmarking reports from APQC in that the key findings section brings in additional research from ARF and includes information concerning the history of market research and development in measuring marketing ROI.